SPE/DOE Improved Oil Recovery Symposium 2002
DOI: 10.2118/75194-ms
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Injection Projects in Brazil: Dimensioning, Field Application and Evaluation

Abstract: Polymer injection in petroleum reservoirs aiming at the enhancement of oilrecovery has been used worldwide for decades. Polymers act basically increasingthe injected water viscosity and reducing the porous media permeability, thenimproving the vertical and areal sweep efficiency. Pilot polymer injection projects for mobility correction are currentlyunderway in three Brazilian fields operated by Petrobras, namely Carmópolis(Sergipe state), Buracica (Bahia state) and Canto do Amaro (Rio Grande … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 7 publications
0
22
0
4
Order By: Relevance
“…The static method is easy and inexpensive. However, the results may not represent the field values because the exposed surface of unconsolidated rock is not the same as the one of a reservoir; the mechanical entrapment component of polymer is not measured and the wettability of the disaggregated rock may be different from that of the reservoir rock (Melo et al, 2002). The second method is measurement of adsorption in the dynamic flow condition by core flooding.…”
Section: Polymer Adsorptionmentioning
confidence: 99%
“…The static method is easy and inexpensive. However, the results may not represent the field values because the exposed surface of unconsolidated rock is not the same as the one of a reservoir; the mechanical entrapment component of polymer is not measured and the wettability of the disaggregated rock may be different from that of the reservoir rock (Melo et al, 2002). The second method is measurement of adsorption in the dynamic flow condition by core flooding.…”
Section: Polymer Adsorptionmentioning
confidence: 99%
“…Melo et al (2001) studied polymer injection projects in Brazil and they expressed that polymer flooding is the best established method of the chemical EOR. Laboratory and field applications have shown that the polymer flooding process is more effectively applied at the early stage of a water flooding project when the mobile oil saturation is still high (Melo et al, 2002). Besides, the research on physical and numerical simulation by specialists and scholars also indicated that the earlier the polymer is injected, the higher the oil recovery factor is enhanced, and the polymer injection profile can be improved effectively when the profile controlling methods are used before or at the initial stage of polymer injection, which makes the effect of polymer flooding better (Feng et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Pattern Optimization by Changing Polymer Throughput Feng et al (2009) showed that good reservoir characterization and dynamic adjustment of injection and production rates contribute significantly to achieve better waterflood performance. The same philosophy becomes more critical for a polymer-flood project because a polymer-flood project is strongly operational-expenditure driven because of the high chemical cost.…”
Section: Firstmentioning
confidence: 99%